2022
DOI: 10.1111/bjd.21701
|View full text |Cite
|
Sign up to set email alerts
|

Ixekizumab rapidly improves inflammatory markers in patients with generalized pustular psoriasis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…4 Recent research demonstrated that ixekizumab rapidly improves inflammatory markers in patients with GPP. 5 GPP of pregnancy occurs most commonly in the second half to third trimester of pregnancy, which is in accordance with our case.…”
supporting
confidence: 92%
“…4 Recent research demonstrated that ixekizumab rapidly improves inflammatory markers in patients with GPP. 5 GPP of pregnancy occurs most commonly in the second half to third trimester of pregnancy, which is in accordance with our case.…”
supporting
confidence: 92%
“…[88][89][90][91] Finally, ixekizumab was found to improve inflammatory markers in patients with GPP with systemic inflammation. 92…”
Section: Ixekizumabmentioning
confidence: 99%
“…Ixekizumab, an interleukin (IL)-17 blockade, has demonstrated effectiveness in the treatment of genital and generalized pustular psoriasis. [ 3 ]…”
mentioning
confidence: 99%